Confirmation of EMIC wave‐driven relativistic electron precipitation. Issue 6 (28th June 2016) - Hendry, Aaron T.; Rodger, Craig J.; Clilverd, Mark A.; Engebretson, Mark J.; Mann, Ian R.; Lessard, Marc R.; Raita, Tero; Milling, David K.
Abstract: Electromagnetic ion cyclotron (EMIC) waves are believed to be an important source of pitch angle scattering driven relativistic electron loss from the radiation belts. To date, investigations of this precipitation have been largely theoretical in nature, limited to calculations of precipitation characteristics based on wave observations and small‐scale studies. Large‐scale investigation of EMIC wave‐driven electron precipitation has been hindered by a lack of combined wave and precipitation measurements. Analysis of electron flux data from the POES (Polar Orbiting Environmental Satellites) spacecraft has been suggested as a means of investigating EMIC wave‐driven electron precipitation characteristics, using a precipitation signature particular to EMIC waves. Until now the lack of supporting wave measurements for these POES‐detected precipitation events has resulted in uncertainty regarding the driver of the precipitation. In this paper we complete a statistical study comparing POES precipitation measurements with wave data from several ground‐based search coil magnetometers; we further present a case study examining the global nature of this precipitation. We show that a significant proportion of the precipitation events correspond with EMIC wave detections on the ground; for precipitation events that occur directly over the magnetometers, this detection rate can be as high as 90%. Our results demonstrate that the precipitation region is often stationary in magnetic local time, narrow in L, and close to the expected plasmapause position. Predominantly, the precipitation is associated with helium band rising tone Pc1 waves on the ground. The success of this study proves the viability of POES precipitation data for investigating EMIC wave‐driven electron precipitation. Key Points: POES‐based electron precipitation triggers most likely caused by EMIC waves detected on the ground EMIC‐IPDP repeatedly triggered at a single MLT closely tied to POES‐detected electron precipitation EMIC waves detected via POES‐detected electron precipitation are primarily helium band IPDP waves